Immunity and international criminal law - Simbeye, Yitiha (Ashgate, 2004)
This groundbreaking debates the issues raised by international crimes. It highlights the two competing international law needs that must be addressed in this situation: the pursuit of international justice and the maintenance of international peace and security.